Ukhuwah Islamiyah Dalam Kehidupan Bermasyarakat - Nurawalia .; Marlina .; M. Amin (CV. ITTC INDONESIA, 2026)
This article discusses the concept of Islamic brotherhood (ukhuwah Islamiyah) as a fundamental principle in building unity and harmony among Muslims. The purpose of this study is to explain the meaning, essence, and foundations of ukhuwah Islamiyah, identify factors that hinder its realization, and propose efforts to strengthen Islamic brotherhood in social life. This study employs a qualitative descriptive approach through literature review by analyzing relevant references such as the Qur’an, Hadith, and scholarly works related to ukhuwah Islamiyah. The results show that ukhuwah Islamiyah is a spiritual and social bond based on faith and piety, which plays a crucial role in maintaining unity, tolerance, and cooperation among Muslims. Factors hindering ukhuwah include arrogance, negative prejudice, unmanaged differences of opinion, and lack of awareness of the importance of brotherhood